2021
DOI: 10.1109/access.2021.3105457
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Deep Brain Stimulation Systems: A General Review

Abstract: Brain Stimulation is now becoming the preferred approach where pharmacological treatment is ineffective in neurological conditions such as Parkinson's Disease (PD), Tourette Syndrome, Addiction disorder, Depression, and Anxiety. The brain can be stimulated by electrical current, light, and sound energy, invasively or non-invasively. The article comprises of pathophysiology in Parkinson's, current pharmacological modalities used for the treatment (along with limitations), and deep brain stimulation as the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Neurostimulation can be performed both in the peripheral and in the central nervous system. While first one is e.g., performed in cases of neuropathic pain ( 18 , 19 ), for nerve regeneration after injury ( 20 ) and to re-establish sensation in people with prostheses ( 21 ), central stimulation serves alleviation of symptoms of e.g., tremor diseases ( 22 24 ), neuropsychiatric disorders ( 25 27 ), pain ( 28 , 29 ) and epilepsy ( 30 32 ). Vagus nerve stimulation (VNS), deep brain stimulation (DBS), and transcranial magnetic stimulation (TMS) are the current methods applied and described in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Neurostimulation can be performed both in the peripheral and in the central nervous system. While first one is e.g., performed in cases of neuropathic pain ( 18 , 19 ), for nerve regeneration after injury ( 20 ) and to re-establish sensation in people with prostheses ( 21 ), central stimulation serves alleviation of symptoms of e.g., tremor diseases ( 22 24 ), neuropsychiatric disorders ( 25 27 ), pain ( 28 , 29 ) and epilepsy ( 30 32 ). Vagus nerve stimulation (VNS), deep brain stimulation (DBS), and transcranial magnetic stimulation (TMS) are the current methods applied and described in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…As an effective treatment method, electrical stimulation plays a vital role in the clinical treatment of brain diseases, such as stroke, 1−3 epilepsy, 4,5 Parkinson's syndrome, 6,7 and Alzheimer's disease. 8,9 It has been reported that transcranial direct current stimulation (tDCS) can noninvasively regulate the neural network in the human brain, 10 induce neural plasticity, 11,12 and stimulate or inhibit 13 the excitability of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…As an effective treatment method, electrical stimulation plays a vital role in the clinical treatment of brain diseases, such as stroke, epilepsy, , Parkinson’s syndrome, , and Alzheimer’s disease. , It has been reported that transcranial direct current stimulation (tDCS) can noninvasively regulate the neural network in the human brain, induce neural plasticity, , and stimulate or inhibit the excitability of neurons. In recent years, transcranial alternating current stimulation (tACS) has also been confirmed to entrain endogenous oscillations by altering gamma activity linked to cognition, thereby enhancing cognitive function or modulating cognitive dysfunction .…”
Section: Introductionmentioning
confidence: 99%